2017
DOI: 10.2500/ar.2017.8.0194
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Environmental Allergies: Comparison of Skin-Prick, Intradermal, and Serum Specific Immunoglobulin E Testing

Abstract: Background:Allergists commonly perform intradermal skin testing (IDST) after negative skin-prick testing (SPT) to comprehensively diagnose environmental allergic sensitization. However, with the availability of modern methods to detect serum-specific immunoglobulin E (ssIgE), it is unclear if ssIgE testing could substitute for IDST.Objective:To determine the efficacy of ssIgE testing and IDST when added to SPT in diagnosing environmental allergic sensitizations.Methods:SPT, IDST, and ssIgE testing to nine comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(62 reference statements)
0
4
1
Order By: Relevance
“…They explained that their findings were due to the presence of protease allergens in the extracts obtained from reported insects, considered the cause of allergy. [15][16][17] Also, in contrast to our study findings, a study done by Kumar R et al, 2012 24 reported that the most common insect allergen was moth followed by mosquito. 24 Patel et al, 2012, has also reported that moth was the most common insect allergen.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…They explained that their findings were due to the presence of protease allergens in the extracts obtained from reported insects, considered the cause of allergy. [15][16][17] Also, in contrast to our study findings, a study done by Kumar R et al, 2012 24 reported that the most common insect allergen was moth followed by mosquito. 24 Patel et al, 2012, has also reported that moth was the most common insect allergen.…”
Section: Discussioncontrasting
confidence: 85%
“…More than one-quarter of the size of the positive control it was scored as 1+; and less than one-quarter of the size of the positive control scored as 0. Scores of 2+ or more were defined as positive reactions 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Calabria and Hagan stated: "For lower potency or non-standardized allergens, the ID skin test may identify a higher percentage of patients with lower levels of clinical sensitivity, and a positive test result may be more clinically relevant" [56]. Several studies in New York City have reported IDT results subsequent to negative SPT, finding among these "non-allergic" patients 20.8% [61] and 24% [62] additional positive antigens.…”
Section: Is Spt Sufficiently Accurate or May Idt Add Valid Information?mentioning
confidence: 99%
“…Once diagnosis of AR has been established and relevant trigger allergens have been identified, it is possible to recommend the appropriate therapies; allergen avoidance, allergen-specific immunotherapy and anti-IgE therapy 5 . Diagnostic strategies that confirm the diagnosis are somewhat problematic, concise diagnosis is based on a detailed patient's history and a diagnostic panel includes in vivo and in vitro tests 6 .…”
Section: Introductionmentioning
confidence: 99%